SUSTAINABLE FISHERMEN'S SETTLEMENT MODEL BASEDON SPACE QUALITY IN FISHERMEN'S HALLPUSONG LAMA VILLAGE LHOKSEUMAWE: MODEL PERMUKIMAN NELAYAN BERKELANJUTANBERBASIS KUALITAS RUANG DI DUSUN NELAYANDESA PUSONG LAMA LHOKSEUMAWE - Rinaldi Mirsa; Yenny Novianti Yenny; Soraya Masthura Hassan; Effan Fahrizal; Nofriadi; Erna Muliana; Sisca Olivia (PT. ROCE WISDOM ACEH, 2026)
The coastal area of Dusun Nelayan, Pusong Lama Village, Lhokseumawe City, is a densely populatedsettlement facing multidimensional challenges, particularly spatial quality degradation caused by limited basic infrastructure and poor waste management. This community service activity aims to implement a Spatial Quality-Based Sustainable Fisherman Settlement Model as an effort to alleviate environmental slum conditions. The method used is a combination of a literature study to strengthen the theoretical foundation of planning and field surveys to collect primary spatial data objectively, systematically, and analytically. The results show that the partner's existing condition is dominated by scattered solid waste and damaged drainage systems and neighbourhood roads. As a solution, this activity successfully produced an integrated physical intervention product in the form of a new site plan design that harmonises residential spaces with fishermen's productive spaces. This spatial quality improvement is reinforced by the design of a three-compartment communal waste management facility and a subsurface communal Wastewater Treatment Plant (WWTP) adapted to coastal characteristics. Spatial comparison indicates that this redesign significantly improves the settlement's functionality, aesthetics, and accessibility, while establishing an essential foundation for community behaviour change and the sustainable development of a waste-recycling-based circular economy.